Neurodevelopmental Abnormalities in Children With PHACE Syndrome. (May 2013) - Tangtiphaiboontana, Jennifer; Hess, Christopher P.; Bayer, Michelle; Drolet, Beth A.; Nassif, Lisa M.; Metry, Denise W.; Barkovich, A. James; Frieden, Ilona J.; Fullerton, Heather J.
Prior case reports have identified neurodevelopmental abnormalities in children with PHACE syndrome, a neurocutaneous disorder first characterized in 1996. In this multicenter, retrospective study of a previously identified cohort of 93 children diagnosed with PHACE syndrome from 1999 to 2010, 29 children had neurologic evaluations at ≥ 1 year of age (median age: 4 years, 2 months). In all, 44% had language delay, 36% gross motor delay, and 8% fine motor delay; 52% had an abnormal neurological exam, with speech abnormalities as the most common finding. Overall, 20 of 29 (69%) had neurodevelopmental abnormalities. Cerebral, but not posterior fossa, structural abnormalities were identified more often in children with abnormal versus normal neurodevelopmental outcomes (35% vs. 0%, P = .04). Neurodevelopmental abnormalities in young children with PHACE syndrome referred to neurologists include language and gross motor delay, while fine motor delay is less frequent. Prospective studies are needed to understand long-term neurodevelopmental outcomes.